The impact of obesity on anxiety disorder and depression in adolescents aged 10 to 19 (Research, Society and Development, 2024)
Obesity is a pathology with multifactorial etiology, therefore there is a need to approach this problem psychologically, considering both the etiology and the maintenance of obesity, cognitive variables (beliefs), affective variables (management of unpleasant emotional states) and environmental variables (customs). and habits). Through studies, it is possible to identify symptoms related to psychological disorders in obese young people, the main ones being anxiety and depression; and in this way it is possible to contribute to improving the family and educational environment through guidance. A literature review was carried out showing the importance of the impact caused on obese adolescents by psychological disorders. The identification of articles occurred free of charge in the databases: Pubmed, VHL, Google Academy and Scielo. Clinical cases published in Portuguese, Spanish and English were sought. The articles included in the research brought various epidemiological data on the topic studied. Through this study it was possible to contribute to effective actions in the clinical practice of diagnosis, treatment and health promotion in obese adolescents.